МЕТОДИЧНІ ПІДХОДИ ДО ОЦІНКИ РІВНЯ ЖИТТЯ НАСЕЛЕННЯ УКРАЇНИ - Todoruk, Sergy; Nykyforak, Valentina (My University, 2018)
Стаття присвячена побудові інтегрального індикатора якості життя населення України. Сконцентрована увага як на можливості поліпшення інформативності й зменшення громіздкості розрахунків окремих індикаторів, пропонованих у вітчизняній науковій літературі для оцінки якості життя населення, так і на двох системних проблемах формування переліків таких індикаторів. Перша проблема – недиференційоване використання індикаторів, друга проблема – використання надмірної кількості аналогічних за змістом показників. Виявлено фактори формування і використання потенціалу поліпшення якості життя населення країни.
METHODICAL APPROACHES TO THE ESTIMATION OF THE LIVING STANDARDS OF THE POPULATION IN UKRAINE
The article is devoted to the construction of an integral indicator of the quality of life of the population in Ukraine. The attention is focused on both the possibilities of improving informality and reducing the cumbersome calculations of individual indicators proposed in the Ukrainian scientific literature for assessing the quality of life of the population, as well as on the two systemic problems of the formation of lists of such indicators. The first problem is the undifferentiated use of indicators, the second problem is the use of excessive amounts of indicators analogous to the content. The factors of formation and use of the potential of improvement of quality of life of the population of the country are revealed.
Keywords: якість життя населення; інтегральний індикатор; ресурсні передумови якості життя; суб’єктивні складові оцінки якості життя; об’єктивні складові оцінки якості життя; оцінки стану якості життя; оцінки поточної ситуації якості життя; quality of life of the population; integral indicator; resource prerequisites of quality of life; subjective components of the assessment of quality of life; objective components of the assessment of quality of life; assessment of the quality of life; assessment of the current situation of quality of life